Comparative study of The Impact of Marriage with Foreigners on Nationality in French and Germany and Iranian Laws - Manuchehr Tavassoli Naini (پژوهشنامه حقوق تطبیقی, 2022)
One of the traditional methods of acquiring citizenship has been based on marriage. In French and German law, this approach has been obsolete for many years. Thus, marriage to foreigners has no effect on nationality anymore. Iranian civil law, using Islamic law and Imamieh Feqh (jurisprudence), has benefited the experiences of law-abiding countries, specifically France and Switzerland. Iranian society has undergone several changes since the year the law was passed. However, the citizenship section of the law is still based on the same traditional view. According to the Iranian laws, if a person from Iran marries a foreign woman, and if an Iranian woman marries a foreign man, according to the principle of “unity of couples”, the nationality of husband is imposed on his wife. In French and German, however, this approach of imposition has been denied for years and marriage to foreigners has no effect on citizenship. The present research compares the laws of the three countries and analyzes the negative effects of imposing the citizenship upon marriage in the Iranian law. The results show that reviewing and revising the old rules on the imposition of citizenship on foreign and Iranian women upon marriage is necessary.